The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1051/0004-6361:20065240
|View full text |Cite
|
Sign up to set email alerts
|

Microquasars as sources of positron annihilation radiation

Abstract: We consider the production of positrons in microquasars, i.e. X-ray binary systems that exhibit jets frequently, but not continuously. We estimate the production rate of positrons in microquasars, both by simple energy considerations and in the framework of various proposed models. We then evaluate the collective emissivity of the annihilation radiation produced by Galactic microquasars and we find that it might constitute a substantial contribution to the annihilation flux measured by INTEGRAL/SPI. We also di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 65 publications
3
77
0
Order By: Relevance
“…The only exception is 4U 0614+091, for which we obtain a higher flux limit (8.7 × 10 −4 ph cm −2 s −1 ), because it is located in a sky region with a lower exposure. Among X-ray binaries (XRBs), microquasars (MQs) are promising galactic positron emitters (see Guessoum et al 2006). We therefore report the 511 keV upper limits for the X-ray Binaries classified as microquasars and detected by IBIS above 20 keV (Table 4).…”
Section: Kev Flux Upper Limit For Compact Sourcesmentioning
confidence: 99%
“…The only exception is 4U 0614+091, for which we obtain a higher flux limit (8.7 × 10 −4 ph cm −2 s −1 ), because it is located in a sky region with a lower exposure. Among X-ray binaries (XRBs), microquasars (MQs) are promising galactic positron emitters (see Guessoum et al 2006). We therefore report the 511 keV upper limits for the X-ray Binaries classified as microquasars and detected by IBIS above 20 keV (Table 4).…”
Section: Kev Flux Upper Limit For Compact Sourcesmentioning
confidence: 99%
“…cosmic rays). Only two astrophysical candidates remain as potentially important contributors: LMXRBs (Prantzos 2004a) or the microquasar variant of that class of sources (Guessoum et al 2006) and the supermassive black hole at the Galactic center (e.g. Cheng et al 2006, Totani 2006, Chernysov et al 2009 and references therein).…”
Section: Pos(integral 2010)018mentioning
confidence: 99%
“…That detection, the first ever of a cosmic radioactivity in γ-rays, showed that nucleosynthesis is still active in the Milky Way; however, the implied large amount of galactic 26 Al (∼2 M per Myr, assuming steady state) was difficult to accomodate in conventional models of galactic chemical evolution if SN were the main 26 Al source (Clayton 1984), since 27 Al would be overproduced in that case; however, if the "closed box model" assumption is dropped and infall is assumed in the chemical evolution model, that difficulty is removed, as subsequently shown by Clayton and Leising (1987).…”
Section: Historical Backgroundmentioning
confidence: 99%
“…A new significant source of positrons seems quite unlikely since various recent reviews (e.g., Dermer & Murphy 2001;Knödlseder et al 2005;Guessoum, Jean, & Prantzos 2006) of the po-tential Galactic positron sources all conclude that supernovae are still the most plausible source, and that other suggested sources, including cosmic-ray interactions, novae, and various exotic processes, all appear to yield much weaker fluxes or are highly uncertain.…”
Section: New Source Of Positrons? -No!mentioning
confidence: 99%